Strategi Komunikasi Persuasif Dinas Kebudayaan Dan Pariwisata Provinsi Sumatera Selatan Dalam Mempromosikan Obyek Wisata Bukit Seguntang - Muhamad Afdoli Ramadoni; Fifin; Tantan Hermansyah (Sadida Islamic Communications and Media Studies, 2022)
The study was entitled persuasive communication strategies for the cultural service and deep tourism promoting Bukit Seguntang to tourists. Regarding the internal activities management Improved quality of the regular tourist destination, competitiveness, based Local characteristics within the framework of tourist attractions, accessibility support, enterprises. Competitiveness and enhanced local tourism abilities. The purpose of this research is to find out What isa persuasive communication strategy for cultural service and tourism in the promotion Sightseeing sightseeing Bukit Seguntang. This type of research is qualitative descriptive research. Technique Data collection using interviews, observation, and documentation. The technique is A in-depth interview that matches the purpose of the research is expected to answer Problem research. Data management techniques and data analysis are performed to answer. The questions are there. As for data analysis covers, data reduction, data presentation, and withdrawal Conclusion. The study led to persuasive communication with the ministry of culture and tourism In some ways to promote mountains of gunk hill tourist attractions. First way Work is the same as the travel agents who bring guests and the nusantara tourists, Across the world to be introduced to the hill mountains. Secondly, it makes leaflets and leaflets Of the hill mountains that contain photographs of the hill plume and graphics later on Promoted to fair both at home and abroad. Third, using printing media, Social media and electronic media in the promotion and dissemination of information around objects. Sightseeing Bukit Seguntang.